2019
DOI: 10.5219/1157
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in consumer preferences when buying dairy products in Slovakia and Russia

Abstract: In spite of geographical and culture differences between examined countries, there can be found similarities in consumer behavior of men and woman and also the similar tendencies on the dairy product market. In the last decade different fields of science concerns with the topic of gender differences more frequently. The article is based on a research of consumers' overall attitude to dairy products in Slovakia and Russia. The important role of gender differences underlines the outcomes of the questionnaire sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…She also states the very strong preference of millennials for domestic, local and regional foods, in contrast to their preference towards foreign foods. Ubrežiová et al (2019) found in a comparative Russian-Slovak study an analogous preference for domestic foods among Slovak consumers on the example of dairy products. The mentioned works (Luomala 2007;Pouta et al 2010;Claret et al 2012;Ubrežiová et al 2019;Petrescu et al 2020), were explicitly devoted to the country of origin of food in different contexts, while the sociological background and reasons for consumer action remained unnoticed.…”
Section: Theoretical Frameworkmentioning
confidence: 82%
See 2 more Smart Citations
“…She also states the very strong preference of millennials for domestic, local and regional foods, in contrast to their preference towards foreign foods. Ubrežiová et al (2019) found in a comparative Russian-Slovak study an analogous preference for domestic foods among Slovak consumers on the example of dairy products. The mentioned works (Luomala 2007;Pouta et al 2010;Claret et al 2012;Ubrežiová et al 2019;Petrescu et al 2020), were explicitly devoted to the country of origin of food in different contexts, while the sociological background and reasons for consumer action remained unnoticed.…”
Section: Theoretical Frameworkmentioning
confidence: 82%
“…Ubrežiová et al . (2019) found in a comparative Russian–Slovak study an analogous preference for domestic foods among Slovak consumers on the example of dairy products. The mentioned works (Luomala 2007; Pouta et al .…”
Section: Theoretical Frameworkmentioning
confidence: 91%
See 1 more Smart Citation
“…When one thinks of large-scale 'consumer research' in the world of products, such as dairy products, one is limited by that which exists, that which works, and of course that which one can afford. It should come as no surprise that the armory of knowledge about consumers and dairy come at once from observations of trends in the market, and at the same time large-scale segmentation studies, wherein the respondent is asked many questions about habits, practices, beliefs, and so forth; for instance, for dairy products, such data ground up into segmentation studies [1][2][3]. The result of both large-scale tracking of consumer behaviors, whether purchase or expressed attitudes, and deep studies of attitudes and behaviors produce for us a bewildering array of numbers, statistics, points to be talked about in presentations, and indeed a panoply of what might be called interesting consumer information.…”
Section: Introductionmentioning
confidence: 99%
“…The agri-food supply chains are characterized by unique characteristics, compared to the conventional supply ones. Therefore, adapted managerial systems based on high product differentiation, seasonality, the short life cycle of perishable goods, specific requirements of transport, storage conditions, and quality and safety in compliance with national and international regulations are needed (van der Vorst, Beulens and van Beek, 2000). One of the most discussed types of supply chains in Slovak agribusiness is a yard sale.…”
Section: Introductionmentioning
confidence: 99%